Knee Extensors Muscle Plasticity Over a 5-Years Rehabilitation Process After Open Knee Surgery - Martin Flück; Claudio Viecelli; Andreas M. Bapst; Stephanie Kasper; Paola Valdivieso; Martino V. Franchi; Severin Ruoss; Jean-Marc Lüthi; Martin Bühler; Helgard Claassen; Hans Hoppeler; Christian Gerber; et al. (Frontiers in Physiology, 2018)
We investigated molecular and cellular parameters which set metabolic and mechanical functioning of knee extensor muscles in the operated and contralateral control leg of 9 patients with a chronically insufficient anterior cruciate ligament (ACL; 26.6 ± 8.3 years, 8 males, 1 female) after open reconstructive surgery (week 0), after ambulant physiotherapy under cast immobilization (week 9), succeeding rehabilitation training (up to week 26), and subsequent voluntary physical activity (week 260). Clinical indices of knee function in the operated leg were improved at 52 weeks and remained at a comparable level at week 260. CSA of the quadriceps (-18%), MCSA of muscle fibers (-24%), and capillary-to-fiber ratio (-24%) in m. vastus lateralis from the ACL insufficient leg were lower at week 0 than reference values in the contralateral leg at week 260. Slow type fiber percentage (-35%) and mitochondrial volume density (-39%) were reduced in m. vastus lateralis from the operated leg at weeks 9 and 26. Composition alterations in the operated leg exceeded those in the contralateral leg and, with the exception of the volume density of subsarcolemmal mitochondria, returned to the reference levels at week 260. Leg-specific deterioration of metabolic characteristics in the vasti from the operated leg was reflected by the down-regulation of mitochondrial respiration complex I-III markers (-41–57%) at week 9. After rehabilitation training at week 26, the specific Y397 phosphorylation of focal adhesion kinase (FAK), which is a proxy for mechano-regulation, was elevated by 71% in the operated leg but not in the contralateral leg, which had performed strengthening type exercise during ambulant physiotherapy. Total FAK protein and Y397 phosphorylation levels were lowered in both legs at week 26 resulting in positive correlations with mitochondrial volume densities and mitochondrial protein levels. The findings emphasize that a loss of mechanical and metabolic characteristics in knee extensor muscle remains detectable years after untreated ACL rupture, which may be aggravated in the post-operative phase by the deterioration of slow-oxidative characteristics after reconstruction due to insufficient load-bearing muscle activity. The reestablishment of muscle composition subsequent to years of voluntary physical activity reinforces that slow-to-fast fiber transformation is reversible in humans.